The effect of Vitamin C in the therapy of haemolactia in dairy cows - Ninković, M; Arsić, S; Žutić, J; Bojkovski, J; Zdravković, N; Panousis, N (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to evaluate the effects of intravenous administration of vitamin C in the therapy of haemolactia in dairy cows. Haemolactia is often of unknown origin, and it can occur due to vitamin C deficiency. The research was carried out on twenty-eight dairy cows having clinical signs of haemolactia, with a clinical score of 2 or 3. The cows of the group A (n=10) were treated intravenously with 2000 mg vitamin C, those of the Group B (n=10) with 3000 mg vitamin C intravenously, whereas cows of group C (n=8) were served as controls and remained untreated. The vitamin C application was once per day intravenously until symptoms disappeared. The appearance of milk and the therapeutic effects of vitamin C were monitored during milking, based on the visual appearance of milk. The average duration of haemolactia in both treated groups A and B was significantly lower (72 h and 68 h, respectively) compared to the control group C (102 h) (p<0.05 for both). Vitamin C was shown to be beneficial in the therapy of haemolactia; no statistical difference was observed regarding the administered doses of vitamin C (2000 vs. 3000 mg). The results prove the importance of vitamin C administration to shorten the duration of haemolactia in dairy cows